Selected Aspects and Determinants of the Slovak Agro-Food Companies' Innovativeness - Moravčíková, Danka; Tkáč, Filip; Mušinská, Kristína (Frontiers in Sustainable Food Systems, 2021)
Sustainability and innovation are seeming to be the key terms and drivers of economic growth and productivity in the contemporary era. The willingness, ability and capacity to innovate is a strategic tool for the Slovak agrifood companies that want to maintain and/or to improve their market position. The aim of this paper is to discuss the selected aspects and determinants of innovative performance of the Slovak agrifood companies and point out key areas and types of innovations, problems influencing their implementation, and assessing their success. The issue of innovation and the “new” role of the agrifood sector have become crucial in the context of transition of the Slovak economy towards more sustainable, therefore they have become important topics of both scientific research and policy agendas. Using a case study method, a questionnaire survey among 99 agrifood companies in Slovakia was carried out to conduct empirical data about the way how they manage, implement and evaluate the innovations. The study demonstrates selected aspects and key determinants which affect the motivation of agrifood companies to innovate as well as selected factors influencing the processes of implementation and management of innovation. The research findings also point out that substantial changes will be required in regulation and support of innovations in the agrifood sector in Slovakia. The study could contribute to help the agrifood companies’ managers to improve the innovation activities and competitiveness of their companies, and it would be also helpful for public administration when developing policies and instruments supporting innovations in the agrifood sector.